2018
DOI: 10.1007/s10661-018-6873-2
|View full text |Cite|
|
Sign up to set email alerts
|

The use of multivariate statistical methods for optimization of the surface water quality network monitoring in the Paraopeba river basin, Brazil

Abstract: This study sought to evaluate and propose adjustments to the water quality monitoring network of surface freshwaters in the Paraopeba river basin (Minas Gerais, Brazil), using multivariate statistical methods. A total of 13,560 valid data were analyzed for 19 water quality parameters at 30 monitoring sites, over a period of 5 years (2008-2013). The cluster analysis grouped the monitoring sites in eight groups based on similarities of water quality characteristics. This analysis made it possible to detect the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 25 publications
0
10
0
4
Order By: Relevance
“…First there were significant (p < 0.05) differences among the stations for each of the 10 variables measured, indicating that water quality declined in the Tunjuelo River as it passed through Bogotá. Calazans et al [45] found a similar result and they concluded that the reduction in water quality along the series of stations was statistically significant for the variables they measured. The month and hour of measurement also significantly (p < 0.05) affected each of the measured variables except fecal coliform, which was not temporally influenced by month or weather.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…First there were significant (p < 0.05) differences among the stations for each of the 10 variables measured, indicating that water quality declined in the Tunjuelo River as it passed through Bogotá. Calazans et al [45] found a similar result and they concluded that the reduction in water quality along the series of stations was statistically significant for the variables they measured. The month and hour of measurement also significantly (p < 0.05) affected each of the measured variables except fecal coliform, which was not temporally influenced by month or weather.…”
Section: Resultsmentioning
confidence: 58%
“…Only TSS and TP significantly contributed to the second component (Figure 4). It is common to observe a relationship between the first [45,47,48] or second [49] principal components and organic matter variables (COD and BOD) and an inverse relationship with DO in PCA analyses of basins contaminated by urban processes. However, as Gigues et al [50] and Pejman et al [51] demonstrate, different behaviors are found in rural basins.…”
Section: Resultsmentioning
confidence: 99%
“…The goal of this paper was to establish fitted equations (prediction models) for determining two water quality parameters, namely chlorophyll-a and ammonia-nitrogen, using other water quality parameters that can be determined easily (temperature, dissolved oxygen, power of hydrogen, suspended solids and electric conductivity). For this purpose a number of statistical methods have been used throughout this research [1,2,3,4,5,6].…”
Section: уводmentioning
confidence: 99%
“…Стандардне процедуре истраживања мерења се често заснивају на анализи великог броја података, покушају идентификације потенцијалних корелација, карактеристичних показатеља, евентуалних груписања података и сличних тенденција. Једна од метода која се често користи као средство за редукцију димензионалности посматраног проблема је анализа главних компонената (АГК), [1,2,3,4,5,6]. Поред примене за редукцију димензионалности посматране проблематике, ова helps to improve the overall interpretation of the gathered information [5].…”
Section: уводunclassified
“…Standard data assessment relies on the investigation of a large number of data, finding various correlations among them, characteristic behaviors, possible clustering and similar tendencies. One of the standard methods often utilized for the reduction of the analyzed sample size is the principal component analysis (PCA), [1,2,3,4,5,6]. In addition to the reduction of the dimensionality, PCA allows enhanced interpretation of the water quality data by helping the identification of spatial and/or temporal trends within the evaluated water quality measurements.…”
Section: Introductionmentioning
confidence: 99%